ANALYSIS OF PERFORMANCE-BASED DESIGN OF 90-STORY HIGH RISE BUILDING WITH BASEMENT IN COOPERATING SOIL-STRUCTURE INTERACTION METHOD - Rosahana Betta, Mia
The response of a structure to earthquake shocks is influenced by the interaction between three interrelated systems namely the structure, foundation, and soil that underlies and surrounds the foundation or underground structure (basement). Soil-Structure Interaction analysis evaluates the collective response of these systems to certain ground movements. Simplified analysis of rigid foundation structures supported on rigid soils has no Soil-Structure Interaction (SSI) effect. While the Soil-Structure Interaction (SSI) effect will be seen with the implementation of spring and damping around the basement and under the basement as a form of representation of soil conditions. The purpose of this study was to determine the performance of structures with and without using the SSI method based on nonlinear analysis consisting of pushover analysis and time history analysis. In this study, the lower structure and upper structure are designed in a separate system (two-stage analysis). Then the spring representing the soil and foundation is calculated based on the sub-structure approach using the impedance function. Furthermore, the two structural systems namely the upper and lower structures that have been installed spring around the retaining wall and the basement base are combined (which is then called the combined structure using the SSI method) and modeled on Perform-3D which is then analyzed nonlinearly. The combined structure in cooperating the SSI method is divided into two models namely the second model and the third model. The second model is a combined structure in cooperating with the SSI method, and a basement designed to meet the requirements of a two-stage analysis. Meanwhile, the third model is a combined structure in cooperating with the SSI method, and a basement designed without meeting the two-stage analysis requirements. The performance obtained from the nonlinear analysis of the combined structure system in cooperating the SSI method is compared with the performance obtained from the nonlinear results of the upper structure which does not use the SSI method with the fixed level at ground level (which is then called the first model). Based on the nonlinear pushover analysis it was found that the structure of the first model had better performance compared to the second and third models. This is because the sheer force on the lower structure floor has decreased for the second and third models due to the modeling of the lower structure and a series of springs and soil attenuation which then gives the opposite force. In addition, based on the nonlinear pushover analysis for the second and third models, plasticization occurs in the basement element due to the moment distribution. In contrast to the nonlinear time history analysis, the second and third models have better performance compared to the first model. There is also no plasticity in the basement element. Thus, the two-stage analysis requirements (which require that plasticization is not permitted on the basement element) are met. Therefore, by using nonlinear time history analysis (the results are more thorough) optimization can be done on a structure that considers the influence of SSI.